Distributed Robust PID Control For Leader Tracking in Uncertain Connected Ground Vehicles With V2V Communication Delay - Fiengo, Giovanni; Lui, Dario Giuseppe; Petrillo, Alberto; Santini, Stefania; Tufo, Manuela (IEEE/ASME transactions on mechatronics, 2019)
The paper addresses the leader tracking problem for a platoon of connected autonomous vehicles in the presence of both homogeneous time-varying parameter uncertainties and vehicle-to-vehicle time-varying communication delay. To this aim, leveraging the multiagent systems (MAS) framework, a novel distributed robust proportional-integral-derivative control is proposed. The stability of the cohesive formation is analytically proved with a Lyapunov-Krasovskii approach by exploiting the descriptor transformation for time-delayed systems of neutral type. The delay-dependent robust stability conditions are expressed as a set of linear matrix inequalities allowing the proper tuning of the proportional, integral, and derivative actions implemented on each of the vehicles within the fleet. Extensive simulation analysis in different driving scenarios confirms the effectiveness of the theoretical derivation.